Complementarities between Grants and Loans - Iimi, Atsushi; Ojima, Yasuhisa (2012)
A debate has emerged over the optimal delivery of official development assistance (ODA) to developing countries: through grants or through concessional loans. While some countries such as Japan provide aid through loans, other countries tend to rely on grants. An endogenous growth model is considered, in which public spending is financed through aid and the donor community can influence a recipient country's growth path by choosing a combination of grants and loans. Empirically, it is found that an increase in the concessionality attached to ODA loans can facilitate recipient countries' economic development. It is also found that grants and loans are complementary with an optimal grant-loan ratio of 1 to 0.2-0.4, depending on the specifications.